Solidarity and diversity in teams: Sketching theoretical and empirical issues - Rybnikova, Irma (Momentum Quarterly, 2015)
For the most part, diversity of the group members has been considered as jeopardizing their solidarity. In the present study, I question this assumption. At first, I consult a range of theoretical concepts from sociology and group psychology which address heterogeneity of groups and its consequences for their solidarity. Whereas some of those concepts state that the fact of heterogeneous group members threatens solidarity among them, other authors assume that heterogeneity can enhance solidarity, given that there is high interdependence between the group members. Mainly drawing on one of these concepts, I undertook an empirical study in one of my lectured courses at the university. Results of the study suggest that even there is a correlation between the solidarity and the heterogeneity of the group members, several ambiguous results can be observed here, such as the difference between the individual and colleagues solidarity in relation to group heterogeneity. On the basis of my theoretical and empirical findings I propose some suggestions regarding future research as well as the activity of trade unions.